A method for producing monoclonal antibodies to human T-cell-receptor beta-chain variable regions. - Callan, M; Reyburn, H; Bowness, P; Ottenhoff, T; Engel, I; Klausner, R; Bell, J; McMichael, A (1993)
Study of the T-cell repertoire in humans has been hampered by the lack of monoclonal antibodies (mAbs) to the T-cell receptor (TCR) variable region (V) gene products. We describe a method for producing mAbs to the human TCR beta-chain V (V beta) gene products in which mice were immunized with a rat basophil cell line (RBL-2H3) transfected with the extracellular domain of the TCR heterodimer fused to the lambda chain of CD3. These cells acted as excellent immunogens for raising anti-TCR mAb and also formed the basis of a rapid screening assay. We generated mAbs against V beta protein of the TCR, showed that these mAbs stained approximately 1% of peripheral blood T cells, and further showed that the mAbs could stimulate proliferation of these T cells. We then characterized the mAbs by amplifying TCR cDNA derived from mAb-stimulated cells and sequencing the beta chain. All clones sequenced used the V beta 7.1 chain, proving conclusively that the mAbs generated were specific for V beta 7.1 subfamily. This method generates mAbs to human TCR V beta proteins efficiently and might allow production of a complete panel of mAbs directed against human TCR V beta proteins.